2016
DOI: 10.12732/ijam.v29i6.8
|View full text |Cite
|
Sign up to set email alerts
|

Study of a One-Dimensional Unsteady Gas Dynamic Problem by Adomian Decomposition Method

Abstract: The system of gas dynamic equations governing the motion of one-dimensional unsteady adiabatic flow of a perfect gas in planer, cylindrical and spherical symmetry is solved successfully by applying the Adomian decomposition method under the exponential initial conditions. The solution of the system of equation is computed up to the five components of the decomposition series. The variation of the approximate velocity, density and pressure of the fluid motion with position and time is studied. It is found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…Woodward et al [14] established an unsteady leakage model by adding a time term to the hole model, and the research found that most of the gas in the pressure vessel leaked in the critical flow state, and the average leakage rate of the gas in the critical flow process could be used to approximately describe the entire leakage process. Singh et al [15] proposed to apply the Adomian decom-position method to solve the one-dimensional unsteady adiabatic gas dynamics equations established in the unsteady leakage model, and the approximate velocity, density and pressure distributions could be obtained. Olorunmaiye et al [16] established an unsteady isothermal pipeline leakage model to calculate the gas leakage process in the pipeline, which was completely cut off, and the research showed the leakage flow rate obtained by the improved model was 18% lower than that of the hole model.…”
Section: Introductionmentioning
confidence: 99%
“…Woodward et al [14] established an unsteady leakage model by adding a time term to the hole model, and the research found that most of the gas in the pressure vessel leaked in the critical flow state, and the average leakage rate of the gas in the critical flow process could be used to approximately describe the entire leakage process. Singh et al [15] proposed to apply the Adomian decom-position method to solve the one-dimensional unsteady adiabatic gas dynamics equations established in the unsteady leakage model, and the approximate velocity, density and pressure distributions could be obtained. Olorunmaiye et al [16] established an unsteady isothermal pipeline leakage model to calculate the gas leakage process in the pipeline, which was completely cut off, and the research showed the leakage flow rate obtained by the improved model was 18% lower than that of the hole model.…”
Section: Introductionmentioning
confidence: 99%
“…They have been successful to capture the shock wave in their solution for planer, cylindrical and spherical symmetries but were unable to investigate the internal structure of shock waves. In 2017, Bajargaan, Patel, and Singh [35] solved the system of gas dynamic equation for unsteady flow of an ideal gas by homotopy analysis method and obtained the shock phenomena but were not able to obtain structure of shock waves. The most general and practical approach will be that in which the complete internal shock structure can be investigated for an unsteady flow of a gas.…”
Section: Introductionmentioning
confidence: 99%